Penyuluhan Penguatan Kapasitas Masyarakat Melalui Eksaminasi Putusan Di Negeri Amahai - Firel E. Sahetapy; Madaskolay V. Dahoklory; Alfian R. Makaruku; Eivandro Wattimury; Elisabeth S. Telussa; Retsky Timisela; Della P. Ajawaila; Alynne H. Matulapelwa (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2026)
Counseling to strengthen community capacity through court decision examinations is a strategic tool for communities to understand and fight for their rights. Negeri Amahai, as one of the Traditional Villages in Maluku, requires legal capacity strengthening, particularly in understanding and following up on court decisions related to the rights of the local community. This community service activity aims to strengthen the capacity of Negeri Amahai residents through legal counseling based on decision examinations, so that the community is able to read, assess, and understand the legal implications of a decision critically. The methods used include preparation, implementation, and evaluation (interactive lectures). The results of the activity show an increase in community understanding of legal rights and obligations, as well as the ability to interpret decisions more accurately. This activity also fosters legal awareness and the courage to fight for their rights legally. Thus, counseling based on decision examinations is an effective approach in building a legally aware community and strengthening access to justice.